2020
DOI: 10.1186/s43046-020-00027-3
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 9 negatively related to clinical outcome of AML patients

Abstract: Background: Acute myeloid leukemia (AML) can modulate toll-like receptor-9 (TLR9) expression and activation. This study was conducted to elucidate the expression of TLR9 in AML patients and its relation to the prognosis of the disease. Results: The study included 40 newly diagnosed AML patients managed in the hospital in addition to 20 sex and age matched normal volunteers as control. TLR9 expression assay was conducted on peripheral blood samples of AML cases before the start of treatment as well as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The present study showed that variant genotypes of the TLR2 rs5743708, TLR4 (rs11536889, rs4986790), and TLR9 (rs187084, rs352140, rs5743836) gene polymorphisms were not associated with AML risk. Our findings are partly similar to those reported by other studies previously [ 14 ]. Thus, no significant difference between cancers and controls for TLR2 rs5743708 SNP was reported in a meta-analysis conducted by Wang et al [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that variant genotypes of the TLR2 rs5743708, TLR4 (rs11536889, rs4986790), and TLR9 (rs187084, rs352140, rs5743836) gene polymorphisms were not associated with AML risk. Our findings are partly similar to those reported by other studies previously [ 14 ]. Thus, no significant difference between cancers and controls for TLR2 rs5743708 SNP was reported in a meta-analysis conducted by Wang et al [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…TLRs play an important role in triggering both the immune response and the inflammatory process. In different cancers, an altered expression of TLR genes had been reported [ 14 ]. Altered TLR signaling was linked to hematopoietic dysfunction and malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings suggest that LST1 overexpression may rewire the signaling network in AML cells, leading to heightened in ammatory responses and immune evasion. Importantly, previous studies have documented the activation of chemokine and Toll-like receptor signaling in AML, promoting leukemia cell proliferation, migration, and survival [31][32][33]. The outcomes of our research offer a new understanding of the molecular pathways implicated in the impact of increased LST1 levels on the progression of AML.…”
Section: Discussionmentioning
confidence: 68%
“…TLR-9 expression in leukemic cells of AML patients with a very low percentage compared to healthy control according to previous a previous study in a neighboring country (Egypt) that contradicted the result of the current study. The expression of TLR-9 was negatively related to the clinical outcome 31 . Cytokines affect the growth of all types of cells in the blood and body cells, which in turn help stimulate the immune response and inflammation 32 .…”
Section: A-roc Curve Of Tlr-9 B-roc Curve Of Tnfα and C-roc Curve Of ...mentioning
confidence: 95%